Peningkatan Wisata Berkelanjutan Di Masyarakat Pedesaan Melalui Penyaluran Buku Saku Daily English For Tourism - Alvian, Ali; Khoyali, Alpan; Rustiana, Dila; Maulana, Erik Subandi; Hilpiana, Lina; Hasanah, Maulia; Subakti, Muhammad; Febriani, Neni; Hartanti, Nurul Fitria; Ulfatunnis; Respa Dewi, Wiwin; Mawarzani, Sapka (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Mastery of English in the tourism industry is one of the important skills that supports the development of the economic sector, especially in tourist villages. In order to support improving English language skills for local communities, we have compiled the book "Daily English for Tourism" as one of the Kuliah Kerja Nyata (KKN) work programs in Buwun Sejati Village. This book is specifically designed to make it easier for people, especially tourism practitioners, to learn vocabulary and daily conversations that are relevant to the needs of interacting with foreign tourists. Distribution of the pocket book “Daily English for Tourism” as an initial solution to overcome the low English language skills of the people in Batu Asak Hamlet, Buwun Sejati Village, especially with the many foreign tourists visiting the village. On this basis, it is important to provide a basic stimulus to improve people’s English language skills. The distribution of the pocket books was carried out on 29-September-2024, which was received symbolically by the secretary of the Buwun Sejati Village tourism awareness group (POKDARWIS) and witnessed by the community who had the opportunity to attend which were, then distributed the following day on 30-September-2024 to society, especially children. The result of the distribution of the “Daily English for Tourism” pocket book is that the people in Batu Asak Hamlet, Buwun Sejati Village, have very high enthusiasm for developing English language skills in order to strengthen the village’s friendly and more professional tourism image.